Angiotensin-converting enzyme insertion/deletion polymorphism associated with allergic rhinitis susceptibility: Evidence from 1410 subjects. (December 2014) - Lin, Hai; Lin, Dong; Zheng, Chun-Quan
Background and objective: Whether the insertion/deletion (I/D) polymorphism of the angiotensin-converting enzyme (ACE) gene increases susceptibility to allergic rhinitis (AR) is still undetermined. Therefore, this meta-analysis was performed to systematically assess the possible association between them. Methods: The OVID, Medline, Embase, Web of Science, CNKI and Wangfang databases were searched to identify the eligible studies focusing on the association between ACE I/D polymorphism and susceptibility to AR. Results: A total of 1410 subjects from six studies were subjected to meta-analysis. In the overall analysis, ACE I/D polymorphism had a statistically significant association with increased AR risk under all genetic models ( p <0.05). In the subgroup analysis by ethnicity, significant elevated AR risks were associated with ACE I/D polymorphism in Asians under all genetic models ( p <0.05) and in Caucasians under under allele contrast, homozygous comparison and recessive models ( p <0.05). In the subgroup analysis by age, ACE I/D polymorphism was associated with significant elevated risks of AR in adults ( p <0.05) but not in children ( p >0.05) under all genetic models. Conclusions: The ACE I/D polymorphism may be a risk factor for AR and studies with large sample size and representative population are warranted to verify this finding.